The PERK/eIF2α/ATF4/CHOP pathway plays a role in regulating monocrotaline-induced endoplasmic reticulum stress in rat liver. (June 2020) - Guo, Yazhou; Guo, Rong; Su, Yongxia; Fu, Jingjing; Wang, Shuai; Kong, Yezi; Wu, Chenchen; Wang, Jianguo; Tan, Chenjian; Mo, Chonghui; Zhao, Baoyu
Abstract: Monocrotaline (MCT) belongs to the category of Pyrrolizdine Alkaloids (PAs), which is one of important hepatotoxic alkaloid in Crotalaria Lin. Apoptosis is one mechanism of toxic responses induced by MCT. However, the underlying mechanism of liver apoptosis caused by MCT through Endoplasmic reticulum (ER) stress continues to be incompletely understood. In this study, we describe the role of ER stress in MCT induced hepatotoxicity in rats. 24 male rats were randomly divided into 3 groups: normal saline group, 45 mg/kg MCT group and 90 mg/kg MCT group. After 48 h of saline/MCT administration, the livers were collected for analysis of ER stress-related proteins by Western blotting. The expression of GRP78, p-IRE1α, ATF6 and caspase-12 showed a dose-dependent increase. PERK/eIF2α/ATF4/CHOP pathway is one of the major ER stress pathways which is required for cell survival. Therefore, through analyzing the effects of MCT on this pathway, we found the protein levels of p-PERK, p-eIF2α, ATF4 and CHOP were increase obviously. All these results indicate that MCT induces ER stress in rat liver. The PERK/eIF2α/ATF4/CHOP pathway is involved in the regulation of MCT-induced ER stress in the liver of rat. Highlights: Monocrotaline induced ERs in the liver of rats. ERs was showed a dose dependent manner during 48 h of treating monocrotaline. The PERK/eIF2α/ATF4/CHOP pathway is involved in the regulation of Monocrotaline-induced ERs in the liver of rats.